Organophosphate Pesticide Exposure and Residential Proximity to Nearby Fields: Evidence for the Drift Pathway - Coronado, Gloria D. (2011)
OBJECTIVES: Residential proximity to pesticide-treated farmland is an important pesticide exposure pathway. METHODS: In-person interviews and biological samples were collected from 100 farmworker and 100 non-farmworker adults and children living in Eastern Washington State. We examined the relationship of residential proximity to farmland to urinary metabolite concentrations of dimethylphosphate (DMTP) and levels of pesticide residues in house dust. RESULTS: DMTP concentrations were higher in farmworkers than non-farmworkers (71 μg/L vs 6 μg/L) and in farmworker children than non-farmworker children (17 μg/L vs 8 μg/L). Compared to non-farmworker households, farmworker households had higher levels of azinphos-methyl (643 ng/g vs 121 ng/g) and phosmet (153 ng/g vs 50 ng/g). Overall, a 20% reduction in DMTP concentration was observed per mile increase in distance from farmland. CONCLUSIONS: Lower OP metabolite concentrations correlated with increasing distance from farmland.